Defect-induced infrared electroluminescence from radial GaInP/AlGaInP quantum well nanowire array light- emitting diodes. (9th November 2017) - Hussain, Laiq; Karimi, Mohammad; Berg, Alexander; Jain, Vishal; Borgström, Magnus T; Gustafsson, Anders; Samuelson, Lars; Pettersson, Håkan
Abstract: Radial GaInP/AlGaInP nanowire array light-emitting diodes (LEDs) are promising candidates for novel high-efficiency solid state lighting due to their potentially large strain-free active emission volumes compared to planar LEDs. Moreover, by proper tuning of the diameter of the nanowires, the fraction of emitted light extracted can be significantly enhanced compared to that of planar LEDs. Reports so far on radial growth of nanowire LED structures, however, still point to significant challenges related to obtaining defect-free radial heterostructures. In this work, we present evidence of optically active growth-induced defects in a fairly broad energy range in vertically processed radial GaInP/AlGaInP quantum well nanowire array LEDs using a variety of complementary experimental techniques. In particular, we demonstrate strong infrared electroluminescence in a spectral range centred around 1 eV (1.2 μ m) in addition to the expected red light emission from the quantum well. Spatially resolved cathodoluminescence studies reveal a patchy red light emission with clear spectral features along the NWs, most likely induced by variations in QW thickness, composition and barriers. Dark areas are attributed to infrared emission generated by competing defect-assisted radiative transitions, or to trapping mechanisms involving non-radiative recombination processes. Possible origins of the defects are discussed.